Regulation 2201/2003 (Brussels II bis) on Recognition and Enforcement of Judgments in Matters of Parental Responsibility - Bordaš, Bernadet (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Regulation 2201/2003 (Brussels II bis) contains unique, special rules on exequatur of  two types of foreign judgments: on the right to visitation and on the return of the child abducted from the state of her/his habitual residence. The paper discusses these rules, with reference to the broader context that includes rules on international jurisdiction of courts of EU Member States in matters of parental responsibility, and rules of exequatur of foreign judgments on parental responsibility in general. The importance of the unique rules are reflected in the fact, that the enforcement of judgments of the courts of EU Member States in these matters are automatic, which means without the need of any special procedure, on the basis of certificates issued by the court of a Member State that has given the judgment, and without review by the Member State of enforcement, thus contributing to the effective exercise of parental responsibility in the child's best interests.
Keywords: automatic exequatur; recognition and enforcement of foreign judgments in matters of parental responsibility; unlawful removal of a child; seeing a child; right of visitation; parental responsibility; Brussels II bis Regulation